Pengaruh Esg, Intellectual Capital Dan Firm Size Terhadap Firm Value (perusahaan sektor energi yang terdaftar di BEI periode 2021-2025) - Shinfia Natania Naswa; Novi Darmayanti; Have Zulkarnaen (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the influence of ESG, Intellectual Capital, and Firm Size on Firm Value in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2025 period. ESG is measured through environmental, social, and governance disclosure scores, Intellectual Capital is measured by the Value Added Intellectual Coefficient (VAIC), Firm Size is measured by the natural logarithm of total assets, and Firm Value is proxied by PBV. The study uses a quantitative approach with a panel data regression method, with samples selected through purposive sampling from energy sector companies listed on the IDX. Data are sourced from annual reports and company sustainability reports. The results of the study are expected to provide empirical evidence regarding the influence of ESG, Intellectual Capital, and Firm Size on Firm Value, both partially and simultaneously, as well as contributing to the development of financial accounting literature and as consideration for management and investors.